Development of Newborn Screening for Pompe Disease - Wuh-Liang Hwu; Yin-Hsiu Chien (MDPI AG, 2020)
Pompe disease is an inborn error of lysosomal degradation of glycogen. The responsible enzyme is acid alpha-glucosidase (GAA) [...]